MEWUJUDKAN BUDAYA ANTI KORUPSI DI KALANGAN MAHASISWA MELALUI KONSEP PENDIDIKAN ANTI KORUPSI DI PERGURUAN TINGGI - Ayu Made Evy Sephia Lestari (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
More and more people are aware of the problem of corruption in Indonesia, and it has become a serious crime that is difficult to appease and generates widespread anger among the people. When anti-corruption efforts don't go as smoothly as they could, the responsibility for solving the problem is left to those who want to work to fix it. However, as the next generation of leaders, we can also help the government deal with this situation. The purpose of this research is to study how anti-corruption education is implemented in universities. The method used in this article is library research, namely reading and comparing various literary works using various library sources such as books, academic journals, encyclopedias, and others. The implementation of this vision, however, cannot be separated from the dissemination of the anti-corruption education curriculum in high schools and tertiary institutions, as well as the role of students in fighting corruption in Indonesia.